Pharmacokinetics, pharmacodynamics and residues depletion of a new enrofloxacin formulation for broiler chickens (Gallus gallus domesticus) : Farmacocinética, farmacodinâmica e depleção de resíduos de nova formulação de enrofloxacina para frangos de corte (Gallus gallus domesticus) - Bonassa, Karina Parra Duarte, 1977- (2016)
Orientadores: Felix Guillermo Reyes Reyes, Miwa Yamamoto Miragliotta